Effect of Jigsaw Technique on the Education of Menstrual Self-care Behaviour to Female Adolescents - Tetti Solehati; Cecep Kosasih (Mashhad University of Medical Sciences, 2020)
Background: It is essential to keep the reproductive organs and surrounding areas hygienic during menstruation to prevent health issues. Inadequate menstrual self-care knowledge, poor attitudes, and behavior among female adolescents can lead to increased morbidity and other complications among them, such as reproductive tract infections. Aim: This study aimed to investigate the effect of the jigsaw technique on menstrual self-care knowledge, attitude, and behavior among adolescents. Method: This quasi-experimental research was performed on 100 female students who were divided into control (n=50) and intervention (n=50) groups (jigsaw intervention) in Al-Musaddadiyah boarding school in Garut, in 2016. The jigsaw technique was performed by dividing the students into small groups of 5-6 where students worked together using interdependent and responsible independent methods to receive education on menstrual self-care. The required data were collected using a questionnaire about knowledge, attitude, and behavior and they were analyzed using independent and paired t-test. A p-value of less than 0.05 was considered statistically significant. Results: Based on the results, mean difference of the intervention group before and after the intervention regarding the level of knowledge, attitude, and behavior were -7,08 (P=0.001), -11.54 (P=0.001), and -16.62 (P=0.001), respectively. While the mean difference of the control group, before and after the intervention regarding the level of knowledge, attitude, and behavior were -0.240 (P=0.06),  -0,180 (P=0.37), -3,4 (p=0.21), respectively. Implications for Practice: The jigsaw method could be effective in increasing menstrual self-care knowledge, attitude, and behavior among female adolescents.